Frequency of severe reactions following penicillin drug provocation tests: A Bayesian meta‐analysis - Cardoso‐Fernandes, António (Clin Transl Allergy, 2021)
BACKGROUND: Patients with a penicillin allergy label tend to have worse clinical outcomes and increased healthcare use. Drug provocation tests (DPT) are the gold‐standard in the diagnostic workup of penicillin allergy, but safety concerns may hinder their performance. We aimed to assess the frequency of severe reactions following a DPT in patients with reported allergy to penicillins or other β‐lactams. METHODS: We performed a systematic review, searching MEDLINE, Scopus, and Web of Science. We included primary studies assessing participants with a penicillin allergy label who underwent a DPT. We performed a Bayesian meta‐analysis to estimate the pooled frequency of severe reactions to penicillin DPTs. Sources of heterogeneity were explored by subgroup and metaregression analyses. RESULTS: We included 112 primary studies which included a total of 26,595 participants. The pooled frequency of severe reactions was estimated at 0.06% (95% credible interval [95% CrI] = 0.01%–0.13%; I (2) = 57.9%). Most severe reactions (80/93; 86.0%) consisted of anaphylaxis. Compared to studies where the index reaction was immediate, we observed a lower frequency of severe reactions for studies assessing non‐immediate index reactions (OR = 0.05; 95% CrI = 0‐0.31). Patients reporting anaphylaxis as their index reaction were found to be at increased risk of developing severe reactions (OR = 13.5; 95% CrI = 7.7–21.5; I (2) = 0.3%). Performance of direct DPTs in low‐risk patients or testing with the suspected culprit drug were not associated with clinically relevant increased risk of severe reactions. CONCLUSIONS: In patients with a penicillin allergy label, severe reactions resulting from DPTs are rare. Therefore, except for patients with potentially life‐threatening index reactions or patients with positive skin tests—who were mostly not assessed in this analysis ‐, the safety of DPTs supports their performance in the diagnostic assessment of penicillin allergy.